PENGARUH MANAJEMEN ASET TERHADAP OPTIMALISASI PEMANFAATAN ASET TETAP DI KABUPATEN KARANGASEM - Mety Andriani Baitanu; Ni Luh Putu Wiagustini (Universitas Triatma Mulya, 2021)
The purpose of this research is to analyze the effect of asset management on optimizing the utilization of fixed assets in Karangasem Regency. This research is an associative research, namely the causality relationship between asset inventory, asset valuation, asset control and control to the level of optimization of fixed assets (land and buildings) owned by Karangasem Regency government. Data collection methods used in this study are through questionnaires / questionnaires. The data analysis technique in this study was quantitative statistical analysis using multiple linear regression models that were completed with the SPSS (Statistical Package for the Social Science) for windows The results of hypothesis testing conducted using multiple linear regression models indicate that: 1). Asset inventory has a positive and significant effect on optimizing the management of fixed assets. 2). Asset valuation has a positive and significant effect on optimizing asset management and 3). Asset control and supervision has a positive and significant effect on optimizing the management of the Karangasem Regency Government assets which shows that any improvement in asset control and supervision will be followed by increased optimization of asset management still the Karangasem Regency government. The implications of this study are a) Asset Inventory has a positive and significant effect on Asset Optimization. This proves that with the implementation of the inventory includes data collection, codification / labeling, grouping and bookkeeping / good administration, it will provide an optimal utilization of assets. b) Asset Valuation has a positive and significant effect on Asset Optimization. Asset valuation conducted by an independent institution is needed by the local government of Karangasem Regency, where the results of this value will be used to determine the value of wealth and information for the application of prices for the assets to be sold. c) Asset Monitoring and Control has a positive and significant effect on Asset Optimization. Supervision and Control have been carried out well by the Karangasem Regency government through the development of the Asset Management Information System.